On the Role of Stock Market for Real Economic Activity: Evidence for Europe - Boriss Siliverstovs; Manh Ha Duong (Deutsches Institut für Wirtschaftsforschung (DIW), 2006)
In this study we have addressed the relationship between the stock market, the measure of real economic activity (represented by the real GDP), the economic sentiment indicator, and real interest rate for the five European countries: Germany, France, Italy, the Netherlands, and the UK. We find that even when accounting for expectations, represented by the economic sentiment indicator, the stock market has certain predictive content for the real economic activity. At the same time, the relationship between the economic sentiment indicator and the real activity seems to be more articulated than that between the latter variable and the stock market. We also have shown that the developments in the national stock markets are explained by the common factor shared by all of them. The greater relative importance of the economic sentiment indicator for the real GDP when compared to that of the stock market can be traced to the fact that the real economic activity is still shaped more by the domestic shocks rather than the global ones, i.e. those reflected in the stock market.
Keywords: G15; E44; 330; Stock market; Real Activity; Economic Sentiment Indicator